Relationship between driving anger, support for counter measure, situational factors and driving behavior among drivers in Malaysia - Abdullah, Nor Azimah Chew; Zakaria, Nazlina (ExcelingTech Publishers, 2018)
This study aims to investigate factors like driving anger, support for counter measures and situational factors affect drivers’ driving behavior. One important reason for studying driver’s aggression is that it has been cited as a frequent contributing factor in traffic collisions. The sample size was collected using convenience sampling as the actual number of driver who drove to work around all the targeted area cannot be identified by the Road Transport Department. The questionnaires weregiven to the driver who passed the targeted area during normal day. Further sample was taken from participants from commuting accidents and safety and health seminars. The data analysis was done using statistical analysis from the Statistical Package for Social Science (SPSS) version 20.0. Analysis of data was done using correlation and multiple regressions to test the hypotheses. The results revealed a positive relationship between driving anger, situational factors and driving behavior. Results of regression showed that driving anger, support for counter measure and situational factors influenced driving behavior. Thus, it is suggested for future research to identify more factors that will affect driving behavior. Thus, the study contributes by providing other potentials antecedents for aggressive driving which includes attitudes, styles and habits of driving.